Predicting the post-fire responses of two forest tree precursors after an autumn fire in mountain fynbos - Caplan, Marc (Department of Biological Sciences, 2017)
This study investigated whether post-fire survival of two fynbos forest precursors Rapanea melanophloeos (L). Mez and Kiggelaria afri.cana L. were dependent on plant size or fire intensity. Two possible mechanisms of size dependent survival were investigated; 1) is fire survival the (ability to resprout) related to concentrations of root stored nonstructural carbohydrates (TNC) or 2) the protection afforded to epicormic buds through the thermal properties associated with bark thickness. Different sized saplings (4-40mm in basal diameter) of both species were planted before a controlled burn in autumn. TNC analysis was performed on a sub-sample of 5 plants from each size class prior to the burn. After the burn discriminant analysis were used to compare which pre- and post-fire variables are the most precise predictors of sprouting. Cambium death was found to be an accurate post fire predictor of mortality of both K. afri.cana and R.melanophloeos saplings. Stem height and basal diameter were good predictors of post-fire mortality of R.melanophloeos. Fire survival of K.afri.cana was independent of size, whereas R. melanophloeos showed a size dependent mortality, and trees with a basal diameter greater than 14mm having a 0. 78 probability of surviving the fire and a 0.67 probability of resprouting. Size dependent fire survival was not related to root TNC concentrations but to the survival of meristematic initials. These findings suggest that current fire management practices which favour cool burns, promote the expansion of forest patches into fynbos.